Resíduo seco de cervejaria na alimentação de frangos de corte - Tesser , Guilherme Luis Silva (2020)
This study aimed to evaluate the dry brewery residue (DBR) and its use in broiler chicken production. In the first experiment, two metabolism tests have been performed. 250 and 100 Cobb 500 birds from 11 to 21 and 31 to 41 days old have been used, respectively. The birds were distributed in a completely randomized design, with four test rations and one reference ration (RR), five repetitions and ten birds for experimental unit (EU). DBR replaced 10; 20; 30 and 40% RR. The experimental period for both tests lasted ten days, being five days of adaptation and five for excreta collection, in which two collections in a day were carried out. The samples of excreta, feed and DBR were dried in forced air oven at 55oC, and subsequently subjected to analysis of dry matter (DM), crude protein (CP), ether extract (EE), gross energy (GE), neutral detergent fiber (NDF), acid detergent fiber (ADF), calcium, phosphorus, potassium, magnesium and sodium. The bromatological composition for the DRB was 91.58% DM, 29.53% CP, 4257 kcal kg-1 of GE, 4.96% EE, 65% NDF, 25.4% ADF, 0.57% calcium, 0.53% phosphorus, 0.14% potassium, 1.16% magnesium and 0.11% sodium, all expressed in raw material. For the period from 11 to 21 days of age, the average values of apparent metabolizable energy (AME), AME corrected by the nitrogen balance (AMEn), gross energy metabolizable energy coefficient (GEMEC) and GEMC corrected by the nitrogen balance (GEMECn) of DBR in raw material, for 11 to 21 days of age, were 2151 kcal kg-1, 1901 kcal kg-1, 50.97% and 45.04%, respectively. For the period from 31 to 41 days of age, the average values of AME, AMEn, GEMC and GEMECn were 1453 kcal kg-1, 1225 kcal kg-1, 34.45% and 29.03%, respectively. In experiment II, 840 day-old Cobb 500 broiler chicks were used, distributed in a randomized design, composed of six levels of inclusion of DBR (0; 2; 4; 6; 8; and 10%) and seven repetitions of 20 birds for EU. In the period from 1 to 21 days of age, there was an increasing linear effect (P <0.05) for the variables weight gain (WG) and feed intake (FI). There was an increasing linear effect (P <0.05) for the FI in the period from 1 to 42 days. At 21 days of age, DBR showed a linear decreasing effect (P <0.05) for cholesterol (CHO) and , there were quadratic effects (P <0.05) for UA and CRE, with minimum levels for minimum responses quadratic (P <0.05) for uric acid (UA), aspartate aminotransferase (AST) and albumin (ALB), in which the maximum response levels picked with inclusion of 7.57%; 6.98%; and 6.30%, respectively. At 42 days of ageof 4.88% and 3.66%, respectively. There was no significant effect (P> 0.05) on the carcass, cuts and liver yield. There was an increasing linear effect (P <0.05) for the protein deposition rate at 21 days of age. DBR can be used in broiler diets from 1 to 21 days of age up to the assessed level of 10%, without affecting the performance or yield of carcasses and cuts in the age of slaughter, as well as the quality of meat.